Descubrir una pasión, proteger un tesoro: herbario UPTC: Entrevista a María Eugenia Morales - Riscanevo , Lida Esperanza; Patiño-Cuervo, Daniela (Uptc, 2022)
This interview recognizes the academic and research contributions of Professor María Eugenia Morales in the context of her professional development at the Universidad Pedagógica y Tecnológica de Colombia. Thus, a biographical and anecdotal journey is made through a dialogue on aspects that delimited her interests, which allowed her to identify the herbarium as a fundamental research field in her career. This space is for her a life project that involves her passion, her dedication and her commitment to preserve and systematize especially the flora of the Eastern Cordillera, with which she seeks to consolidate it as a cultural and scientific heritage at the service of research in the area of biological sciences at national and international level. Finally, the work of the teacher-trainer for research and its impact in radiating the commitment in the theoretical and experimental development of botany is highlighted.